2024
DOI: 10.3390/biomedicines12020441
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Exosomes Derived from M2 Macrophages with Enhanced Odontogenesis, Neurogenesis and Angiogenesis for Regenerative Endodontic Therapy: An In Vitro and In Vivo Investigation

Yujie Wang,
Jing Mao,
Yifan Wang
et al.

Abstract: Introduction: Exosomes derived from M2 macrophages (M2-Exos) exhibit tremendous potential for inducing tissue repair and regeneration. Herein, this study was designed to elucidate the biological roles of M2-Exos in regenerative endodontic therapy (RET) compared with exosomes from M1 macrophages (M1-Exos). Methods: The internalization of M1-Exos and M2-Exos by dental pulp stem cells (DPSCs) and human umbilical vein endothelial cells (HUVECs) was detected by uptake assay. The effects of M1-Exos and M2-Exos on DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Wang and colleagues compared exosomes from M1 and M2 macrophages with respect to their pro-angiogenic properties. They could show that, compared to M1-Exos, M2-Exos showed a higher osteogenic and angiogenic potential [167]. The group of Fang showed that exosomes from human umbilical cord MSCs (hUC-MSC) promoted angiogenesis and osteogenesis via miR-21-5p [168].…”
Section: Msc Exosomes In Bone Angiogenesis and Vascular Developmentmentioning
confidence: 99%
“…Wang and colleagues compared exosomes from M1 and M2 macrophages with respect to their pro-angiogenic properties. They could show that, compared to M1-Exos, M2-Exos showed a higher osteogenic and angiogenic potential [167]. The group of Fang showed that exosomes from human umbilical cord MSCs (hUC-MSC) promoted angiogenesis and osteogenesis via miR-21-5p [168].…”
Section: Msc Exosomes In Bone Angiogenesis and Vascular Developmentmentioning
confidence: 99%